One-way valve for chest drainage: Experimental evaluation - Carrera, Carlos; Iriondo, Nilsa; Rubí, Francisco; Cestaro, Leticia (Cirugía del Uruguay, 1975)
The present work discusses the design and usage of a unidirectional valve for drainage of the pleural cavity in experimental surgery. It is designed in a duckpeak shape, with 2 latex valves, 0.5 mm thick and 5.05 cm2 surface. Its critica! leve! of opening ranges between a pressure of 0.3 and 1 centimeter of water. Its output depends upon the gauge of the adapter (a 6 mm tube was used) and upon the fluid or gaseous supply to be drained. It has been tested on 15 animals with hypertensive pneumothorax, either provoked or after carinal surgery. It has proved to be efficient and easy to manage. Possible clínica! applications of this device are suggested.